DEVELOPMENT AND REALIZATION OF STUDENTS’ SUBJECTNESS IN EDUCATIONAL ACTIVITIES - Svetlana B. Rybakova (Высшее образование в России, 2022)
The article dwells on a problem of genesis and realization of students’ subjectness in educational activity. The questions concerning practical organization and the content of subject-subject relations in higher school are considered. The article also touches upon the issue of criteria of subjectness and pattern of its development in educational activities.